Feeding Potential of Menochilus sexmaculatus (Fabricius) Against Sucking Insect Pests - Aslam Bukero,; Maqsood Anwar Rustamani,; Ghulam Hussain Abro,; Abdul Mubeen Lodhi, (Journal of Basic & Applied Sciences, 2014)
This laboratory experiment was conducted to find out the feeding performance and larval development of Menochilus sexmaculatus (Fabricuis) on Aphis gossypii (Glov.), Bemisia tabaci (Ginn.) and Amrasca biguttula biguttula (Distant) at 26 ± 2ºC temperature and 65 ± 5% relative humidity. The result indicated that the 3rd and 4th instar larvae of the beetle consumed 76.20 ± 3.44 and 79.7 ± 0.77 nymphs of A. gossypii /day followed by (23.0 ± 0.77) and (23.4 ± 0.75) nymphs of B. tabaci and (19.73 ± 1.17) and (21.55 ± 0.77) nymphs of A. b. biguttula, respectively as compared to 1st and 2nd instar larvae. Adult female consumed maximum (101.0 ± 0.55) nymphs of A. gossypii /day followed by (26.90 ± 0.27) nymphs of B. tabaci and (22.16 ± 0.20) nymphsof A. b. biguttula as compared to male. The result further revealed that the 4th instar larva consumed highest number 159.4 ± 7.35 of A. gossypii nymphs during its life span followed by (93.8 ± 3.02) and (86.2 ± 3.09) nymphs of B. tabaci and A. b. biguttula, respectively. Similarly, the adult female devoured highest number of nymphs (3040.2 ± 26.4) of A. gossypii followed by B. tabaci (807.0±8.1) and A. b. biguttula (664.98±6.0) during its life span as compare to male. The shortest life span was recorded on A. gossypiias compared to A. b. biguttula and B. tabaci, There was highly significant difference in consumption rate and development period of larvae and adult beetles on different prey species (P<0.05).